THE EFFECT OF INVOLVEMENT IN SELECTING STRATEGIC INITIATIVES AND STRATEGIC INITIATIVE REPORT ON DIVISION MANAGERS’ PERFORMANCE EVALUATION USING BALANCED SCORECARD - Syaiful Anas; Mahfud Sholihin (Journal of Economics, Business, and Accountancy Ventura, 2013)
This study attempts to analyze the effect of involvement in the selection of strategic initiativesand the strategic initiatives report on strategic initiatives and managerial performance evaluationin the Balanced Scorecard (BSC) context. It is argued that managers’ involvement in theselection of strategic initiatives will increase the tendency to arrive at a conclusion that is consistentwith their preference especially when they receive complex information. In addition toit, strategic initiatives report is expected to reduce the effect of motivated reasoning by providingstrong evidence on the initiative’s effectiveness. Using a 2×2 between subjects of experimentinvolving 63 undergraduate students, it was found that the involvement of the managershas no significant effect on both the evaluation of strategic initiative effectiveness and divisionmanager’s performance. Furthermore, it was also found that the strategic initiative report hasonly effect on division manager’s performance but at the unexpected direction. Finally, thestudy cannot provide evidence on the interaction effect of the two independent variables.